Gambaran Penerapan Ketepatan Identifikasi Pasien pada Perawat Pelaksana di Rumah Sakit - Sofyanudin Sofyanudin; Muh Abdurrouf; Dyah Wiji Puspita Sari (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Patient safety is a crucial component of healthcare services that must be implemented consistently, one of which is through proper patient identification. Errors in the patient identification process can lead to various safety risks, such as medication errors and inappropriate nursing interventions. This study aimed to describe the correct implementation of patient identification by nurses in a hospital setting. The study employed a descriptive design with a quantitative approach. The research population consisted of all 94 nurses at Sultan Agung Islamic Hospital, and total sampling was applied so that the entire population served as respondents. Data were collected through observation using an assessment instrument for the accuracy of patient identification consisting of 13 statements. Data analysis was conducted univariately to describe the distribution of frequencies and percentages. The results showed that most nurses demonstrated a good level of accuracy in performing patient identification. The majority of respondents were female, had a professional nursing (Ners) educational background, and had a moderate length of work experience. These findings indicate that the implementation of patient identification in the hospital has generally been carried out well. Nevertheless, further efforts are still needed to improve and strengthen nurses’ compliance with patient safety standards, particularly among those in the fair and poor categories. The results of this study are expected to serve as a basis for evaluation and continuous improvement efforts in patient safety, especially related to patient identification in inpatient care units.